Use of ultrasonography in reduction of isolated zygomatic arch fracture - Dhungel, Safal; Singh, Ashutosh Kumar (Journal of Chitwan Medical College, 2020)
Background: Isolated zygomatic arch fractures, managed by closed methods, can be inadequate leading to facial asymmetry. Assessment of the reduction and ensuring correct alignment of fractured fragments in the operation table always avoids next surgery. This study aims to determine intraoperative, adequacy of reduction of by use of ultrasound in isolated zygomatic arch fracture. Methods: During the closed reduction of isolated zygomatic arch linear probe of ultrasound was used to check the continuity of the echogenic line. The intraoperative ultrasound finding was compared with the gold standard CT scan. Results: Ultrasound has 100% sensitivity and 80 % specificity. It also has high precision and accuracy to determine the reduction of the fractured bone. Conclusions: Ultrasound is a handy tool in the reduction of zygomatic arch fracture. It not only shows but also guides to adequate reduction.